2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--31986
|View full text |Cite
|
Sign up to set email alerts
|

A Real-World Approach to Introducing Sustainability in Civil Engineering Capstone Design

Abstract: She coordinates both the civil and multidisciplinary engineering senior design projects. These projects are the culmination of the undergraduate engineering experience. Students design an innovative solution to a complex problem. She has recruited professional sponsors who mentor the civil engineering design projects. The projects expose the civil engineering students to real world design problems. The students gain first hand experience communicating professionally, developing schedules, meeting deadlines and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Given this complexity, the collaboration of the university with its stakeholders is essential for both decision-making and implementation in everything related to sustainability. Among these collaboration agents are: (1) other universities, such as, for example, the collaboration between universities in Sweden and Tanzania to introduce new pedagogies in the latter [34]; the network of 19 European universities for the development of Capstone Projects [5]; or the consortium of French universities to respond to the initiative of the government to deploy SDGs in agricultural engineering [14]; (2) other disciplines within the same university, such as the case of chemical engineering students who are asked to carry out interdisciplinary projects that they must then explain to students from other areas [25], or the case in which a subject is divided into humanities and engineering and taught by an interdisciplinary team of teachers [30]; (3) pre-university institutions, such as the incorporation of an algae-based curriculum in the last year of secondary school and first year of undergraduate studies [28], or the project at a Russian university for the prediction of ecological damage and the resolution of ecological security problems [4]; (4) the business and industrial network, as for instance, to develop the End of Degree Projects with external mentors [26], as a destination for the analysis of gender inequalities in product design at the Japanese university [12], to train students while working [13] or, as in the case of the university in Tanzania, to carry out their projects in an electricity company [34]; (5) technology centers, where simulations are carried out [18]; (6) governments, as in the collaboration with the University of Tanzania [34], or the French public initiative for a new curriculum [14]; (6) non-governmental organizations, which provide fieldwork for students [9], and, finally, (7) the demanded collaboration with accreditation bodies and other quality institutions to discuss how to ensure and integrate academic outcomes with appropriate and ethical practices [23], to improve degrees in Africa and gain in mobility [16], or to collaborate, together with the other institutions involved, in determining the most appropriate attributes, competencies, and learning outcomes of an engineering graduate to help achieve the SDGs [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given this complexity, the collaboration of the university with its stakeholders is essential for both decision-making and implementation in everything related to sustainability. Among these collaboration agents are: (1) other universities, such as, for example, the collaboration between universities in Sweden and Tanzania to introduce new pedagogies in the latter [34]; the network of 19 European universities for the development of Capstone Projects [5]; or the consortium of French universities to respond to the initiative of the government to deploy SDGs in agricultural engineering [14]; (2) other disciplines within the same university, such as the case of chemical engineering students who are asked to carry out interdisciplinary projects that they must then explain to students from other areas [25], or the case in which a subject is divided into humanities and engineering and taught by an interdisciplinary team of teachers [30]; (3) pre-university institutions, such as the incorporation of an algae-based curriculum in the last year of secondary school and first year of undergraduate studies [28], or the project at a Russian university for the prediction of ecological damage and the resolution of ecological security problems [4]; (4) the business and industrial network, as for instance, to develop the End of Degree Projects with external mentors [26], as a destination for the analysis of gender inequalities in product design at the Japanese university [12], to train students while working [13] or, as in the case of the university in Tanzania, to carry out their projects in an electricity company [34]; (5) technology centers, where simulations are carried out [18]; (6) governments, as in the collaboration with the University of Tanzania [34], or the French public initiative for a new curriculum [14]; (6) non-governmental organizations, which provide fieldwork for students [9], and, finally, (7) the demanded collaboration with accreditation bodies and other quality institutions to discuss how to ensure and integrate academic outcomes with appropriate and ethical practices [23], to improve degrees in Africa and gain in mobility [16], or to collaborate, together with the other institutions involved, in determining the most appropriate attributes, competencies, and learning outcomes of an engineering graduate to help achieve the SDGs [9].…”
Section: Discussionmentioning
confidence: 99%
“…The strategies described in the papers were very varied, depending upon the possibilities of a greater approach to reality: Practice-based Education (PBE), in which students learn by working [13]; Internship (IS) [23]; Challenge-based Learning [4,5,14,15,31,34]; Problem-based Learning [11,16,23,25,33]; the theory for inventive problem-solving (TRIZ) [4] (all of them based in projects); Service learning (SL) [23,25]; laboratory experiments and simulations [11,18,28]. Some of these strategies were used to work on SDGs in the Capstone Projects [5,15,23,26] and in some cases, the best solutions were implemented in developing countries [31]. Others supported strategies focused on developing rubrics that help students learn the different dimensions of sustainability, set expectations for sustainable design, and self-assess the extent to which they can apply these principles in their projects [27] or rubrics that are used to evaluate student work to identify opportunities to improve their learning [32], Flipped Classroom (FC) [18], or conferences and seminars [10,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported raising the bar of sustainability by engaging a sustainability expert could be a viable option for the instructor to adopt sustainability in their class. Scott et al (2013) adopted sustainability component in senior design by a real-world project [3]. The authors concluded that sustainability impacted students critical thinking and increased knowledge, but it also yielded a high workload for the students and faculty.…”
Section: Introductionmentioning
confidence: 99%
“…Capstone requires students to implement multiple engineering concepts from their education and develop skills related to secondary and primary information gathering, synthesis, and application [33], [34]. Prior work has suggested that capstone courses can be used to encourage students to gain real-world stakeholder engagement and contextual investigation skills [35], [36], such as developing design requirements based on stakeholder needs and contextual factors [33]. However, engineering students incorporate broader global, social, economic, and environmental contextual factors into their design processes to varying degrees [37].…”
Section: Introductionmentioning
confidence: 99%